Political Dialectic and Islamic Education Policy: A Study on The Dynamics of Regulation and Autonomy of Islamic Universities in Indonesia - Zeni Murtafiati Mizani; Sabarudin; Ahmad Arifi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The transformation of Islamic Religious Higher Education Institutions (PTKI) in Indonesia highlights ongoing tensions between state regulation and academic autonomy at both PTKIN and PTKIS. This study analyzes how state regulations influence PTKI/PTKIS autonomy, explores the politics of knowledge in scientific integration, identifies autonomy imbalances, and proposes a dialectical framework for educational governance. Using a qualitative case study approach, the research examines policy documents and institutional practices through the perspectives of Michel Foucault, Antonio Gramsci, and Jürgen Habermas. Key findings include: (1) state regulation systematically shapes and restricts PTKI/PTKIS autonomy, particularly in curriculum and academic standards; (2) scientific integration emerges from negotiations between policy and institutional response; (3) autonomy imbalances exist between PTKIN and PTKIS, especially regarding resources and governance; and (4) the interplay of politics, regulation, and autonomy forms a dynamic dialectic, positioning autonomy as negotiated rather than absolute. This study’s novelty lies in its integrated analysis of regulation, institutional practice, and epistemic construction, and its proposal for a deliberative, collaborative governance model to promote more equitable and adaptive Islamic higher education. Abstract Transformasi Perguruan Tinggi Keagamaan Islam (PTKI) di Indonesia menunjukkan ketegangan antara regulasi negara dan otonomi akademik, baik pada PTKIN maupun PTKIS. Penelitian ini bertujuan untuk menganalisis dinamika regulasi negara terhadap otonomi PTKI/PTKIS, mengkaji politik pengetahuan dalam integrasi keilmuan, mengungkap ketimpangan otonomi, serta merumuskan pola dialektika sebagai dasar pengembangan tata kelola pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus melalui analisis dokumen kebijakan dan praktik kelembagaan, dengan kerangka analisis Michel Foucault, Antonio Gramsci, dan Jürgen Habermas. Hasil penelitian menunjukkan: pertama, regulasi negara secara sistemik membentuk sekaligus membatasi otonomi PTKI/PTKIS, termasuk dalam kurikulum dan standar akademik; kedua, integrasi keilmuan berkembang sebagai hasil negosiasi antara kebijakan dan respons institusi; ketiga, terdapat ketimpangan otonomi antara PTKIN dan PTKIS, terutama dalam sumber daya dan tata kelola; keempat, relasi politik, regulasi, dan otonomi membentuk dialektika dinamis yang menempatkan otonomi sebagai hasil negosiasi, bukan kebebasan absolut. Kebaruan penelitian ini terletak pada integrasi analisis regulasi, praktik kelembagaan, dan konstruksi epistemik secara simultan, serta tawaran model tata kelola kolaboratif berbasis deliberatif untuk memperkuat pendidikan tinggi Islam yang lebih adil dan adaptif. Keywords: Islamic Education Policy; Higher Education Policy; PTKIN; PTKIS; Integration of Knowledge